2022
DOI: 10.1097/jcma.0000000000000708
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative effect of taxifolin on gentamicin-induced ototoxicity via down-regulation of apoptotic pathways in mouse cochlear UB/OC-2 cells

Abstract: Background: Taxifolin is a flavanonol with efficacious cytoprotective properties, such as anti-inflammatory, antioxidant, anticancer, hepatoprotective, and nephroprotective effects. However, the potential protective effects of taxifolin against gentamicin-induced ototoxicity have not been confirmed. In this study, the possible mechanisms underlying the effects of taxifolin on gentamicininduced death of UB/OC-2 cochlear cells were investigated. Methods: Mouse cochlear UB/OC-2 cells with or without taxifolin pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…Previous research has shown that TA may reduce inflammation by inhibiting the NF-κB signaling pathway through ROS suppression [ 25 , 56 ]. Consistently, TA prevents gentamicin-induced apoptotic cell death mediated by the mitochondrial pathway in the kidney [ 57 ]. Thus, TA’s anti-inflammatory and anti-apoptotic properties could be related to its ROS-suppressing properties.…”
Section: Discussionmentioning
confidence: 96%
“…Previous research has shown that TA may reduce inflammation by inhibiting the NF-κB signaling pathway through ROS suppression [ 25 , 56 ]. Consistently, TA prevents gentamicin-induced apoptotic cell death mediated by the mitochondrial pathway in the kidney [ 57 ]. Thus, TA’s anti-inflammatory and anti-apoptotic properties could be related to its ROS-suppressing properties.…”
Section: Discussionmentioning
confidence: 96%
“…The anti-apoptosis effect of TAX reported in this study could be directly explained by the attenuation of oxidative stress and inflammation. In support of these findings, a recent study reported that TAX prevented gentamicin-induced apoptosis in mouse cochlear cells by preventing ROS-induced alteration in MMP and ameliorating Bax and Bcl-2 expression [46]. The ability of TAX to prevent oxidative stress and apoptosis has also been reported in human RPE [24] and alcohol-induced acute hepatic injury in mice [27].…”
Section: Discussionmentioning
confidence: 61%
“…GM action on cochlear tissues can cause a large amount of ROS to be generated in the mitochondria of HCs, activation of caspase 3 and induction of apoptosis [ 32 , 33 ]. SAL protects PC-12 cells by inhibiting Aβ 1-42-induced cytotoxicity and mitochondria-mediated endogenous caspase apoptotic pathways [ 34 ].…”
Section: Discussionmentioning
confidence: 99%